Categorisation of the offshore wind production system. (13th April 2022) - Lerche, Jon; Neve, Hasse; Wandahl, Søren; Gross, Allan
This paper investigates and describes the production system characteristics for offshore wind turbine assembly and compares it to manufacturing and construction. It requires understanding of the organisations, products and processes to categorise the production system for offshore wind farm assembly. This study compares explorative cases with literature describing the production system characteristics from production and manufacturing domains. The categorisation is completed by comparing product-process first and then product-organisation. To understand the identified differences, the results are displayed in matrixes with manufacturing and construction characteristics from the literature, compared with field notes, observations and archived data from wind turbine assembly cases. The results show offshore wind turbine assembly as a hybrid production system in this comparative study. The comparison contributes to the novel understanding of the wind industry and is theory building within operations research. It establishes a baseline for further operational research within the offshore wind domain.